(Bio)manufactured Solutions for Treatment of Bone Defects with an Emphasis on US‐FDA Regulatory Science Perspective. Issue 4 (5th January 2022) - Ghelich, Pejman; Kazemzadeh-Narbat, Mehdi; Hassani Najafabadi, Alireza; Samandari, Mohamadmahdi; Memić, Adnan; Tamayol, Ali
Abstract : Bone defects, with second highest demand for surgeries around the globe, may lead to serious health issues and negatively influence patient lives. The advances in biomedical engineering and sciences have led to the development of several creative solutions for bone defect treatment. This review provides a brief summary of bone graft materials, an organized overview of top‐down and bottom‐up (bio)manufacturing approaches, plus a critical comparison between advantages and limitations of each method. Additive manufacturing techniques and their operation mechanisms in detail are specifically discussed. Next, the hybrid methods and promising future directions for bone grafting are reviewed while giving a comprehensive United States Food and Drug Administration (US‐FDA) regulatory science perspective, biocompatibility concepts and assessments, and clinical considerations to translate a technology from a research laboratory to the market. The topics covered in this review can potentially fuel future research efforts in bone tissue engineering, and perhaps can also provide novel insights for other tissue engineering applications. Abstract : This review emphasizes on the fabrication strategies for bone tissue engineering and their United States Food and Drug Administration regulatory perspective. Bone biology and materials for engineering bone grafts are discussed. (Bio)manufacturing approaches are critically reviewed. Subsequently, a road map for United States Food and Drug Administration conformance is provided.